2016
DOI: 10.1109/jphot.2016.2524210
|View full text |Cite
|
Sign up to set email alerts
|

Etching Process Related Changes and Effects on Solid-Core Single-Mode Polymer Optical Fiber Grating

Abstract: Etching process related material and mechanical changes on solid-core singlemode polymer optical fiber (POF) and their influence on the characteristic properties of polymer fiber Bragg gratings (PFBGs) are studied. A poly(methyl methacrylate)-based POF is etched to different diameters, and it is experimentally demonstrated that etching can lead to a change in the Young's modulus of the fiber. It is found that etching process induced material changes of the polymer fiber can enhance the reflectivity and inheren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…If there are different materials on the fiber composition, an approximation for the resulting Young Modulus can be made through Eq. (2) [43]:…”
Section: Resultsmentioning
confidence: 99%
“…If there are different materials on the fiber composition, an approximation for the resulting Young Modulus can be made through Eq. (2) [43]:…”
Section: Resultsmentioning
confidence: 99%
“…Fig. 1(a) shows the measured reflectivity pattern of polymer FBG with different diameters [6]. From the figure it is observed that, a reflectivity of 79.42 % is observed within 60 seconds of exposure for an un-etched POF with a diameter of 185 μm.…”
Section: High Sensitivity and High Reflectivity Bragg Gratingsmentioning
confidence: 98%
“…The photosensitivity of the latter introduction can be more stable. In addition, the photosensitivity can also be enhanced by the straining during the grating inscription [61] or the etching of photosensitive POF cladding [47,70]. As shown in Table S1, the change of the refractive index by radiation is ranged from 10 −5 to 10 −3 .…”
Section: Pof Gratingsmentioning
confidence: 99%
“…Although the control of the writing time is a complicated process, the reduction of the inscription time is the development trend for the improvement of writing efficiency. Figure 2 shows the historical evolution of inscription time of POF Bragg gratings [44,46,52,64,65,68,70,81,85,86,91,92,95,99,102,106,112,115,120,121,126,127,132,140]. …”
Section: Techniques and Issues Of Fabricating Pof Gratingsmentioning
confidence: 99%
See 1 more Smart Citation